Numerical Analysis of Copper-Indium-Gallium-Diselenide-Based Solar Cells by SCAPS-1D - S. Ouédraogo; F. Zougmoré; J. M. Ndjaka (International Journal of Photoenergy)
We used a one-dimensional simulation program Solar Cell Capacitance Simulator in 1 Dimension (SCAPS-1D) to investigate Copper-Indium-Gallium-Diselenide- (CIGS-) based solar cells properties. Starting with a conventional ZnO-B/i-ZnO/CdS/CIGS structure, we simulated the parameters of current-voltage characteristics and showed how the absorber layer thickness, hole density, and band gap influence the short-circuit current density (Jsc), open-circuit voltage (Voc), fill factor (FF), and efficiency of solar cell. Our simulation results showed that all electrical parameters are greatly affected by the absorber thickness (w) below 1000 nm, due to the increase of back-contact recombination and very poor absorption. Increasing hole density (p) or absorber band gap (Eg) improves Voc and leads to high efficiency, which equals value of 16.1% when p = 1016 cm−3 and Eg=1.2 eV. In order to reduce back-contact recombination, the effect of a very thin layer with high band gap inserted near the back contact and acting as electrons reflector, the so-called back-electron reflector (EBR), has been investigated. The performances of the solar cells are significantly improved, when ultrathin absorbers (w < 500 nm) are used; the corresponding gain of Jsc due to the EBR is 3 mA/cm2. Our results are in good agreement with those reported in the literature from experiments.